The enemy within: the secret war against the miners. 4th ed. - Milne, Seumas (London, 2014)
"Margaret Thatcher branded the leaders of the 1984-85 miners strike “the enemy within.” With the publication of this book, the full irony of that accusation became clear. Seumas Milne revealed for the first time the astonishing lengths to which the government and its intelligence machine were prepared to go to destroy the power of Britain’s miners’ union. There was an enemy within. It was the secret services of the British state, operating inside the NUM itself.